Organizational Culture, Job Satisfaction, and Employee Performance (Case Study in PT. GMT Jember) - Yulinartati Yulinartati; Eras Wike Dania (Perkumpulan Praktisi Akuntansi Indonesia, 2020)
The study aims to analyze the influence of organizational culture and job satisfaction to employee performance with organizational commitment as intervening variable at PT. GMT Jember. In accordance with the above objective in this study formulated the five hypothesis. Samples obtained 30 respondents. The conclusion to be drawn from this study that the organizational culture and job satisfaction, and a significant positive effect on employee performance. Commitment to the organization and significant positive effect on employee performance. Organizational commitment is also positive and significant relation between cultural organization against employee performance. Organizational commitment influential significant positive and also mediate the relationship between job satisfaction to employee performance. Suggestions for further research, the sample should increase and expand the scope of the study, considers the other variables that are closely related to the variables in this study.